2021
DOI: 10.1128/mbio.01885-21
|View full text |Cite
|
Sign up to set email alerts
|

Symbiont-Mediated Protection of Acromyrmex Leaf-Cutter Ants from the Entomopathogenic Fungus Metarhizium anisopliae

Abstract: In some plants and animals, beneficial microbes mediate host immune response against pathogens, including by serving as defensive symbionts that produce antimicrobial compounds. Defensive symbionts are known in several insects, including some leaf-cutter ants where antifungal-producing Actinobacteria help protect the fungal mutualist of the ants from specialized mycoparasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…The defensive ectomicrobiome of leaf-cutting ants, especially the key bacterial members Pseudonocardia and Streptomyces , can produce antifungal compounds to inhibit fungal spore germination ( 25 , 26 , 28 ). Strains of L. plantarum have been developed as potential probiotics in the food industry ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defensive ectomicrobiome of leaf-cutting ants, especially the key bacterial members Pseudonocardia and Streptomyces , can produce antifungal compounds to inhibit fungal spore germination ( 25 , 26 , 28 ). Strains of L. plantarum have been developed as potential probiotics in the food industry ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to per os infections of insects by pathogenic bacteria and viruses, fungal pathogens infect insects through spore germination on host cuticles and the penetration of exoskeletons ( 20 , 21 ). Similar to the protective barrier functions of the human skin and plant phyllosphere microbiotas ( 22 24 ), diverse insects, such as ants, wasps, and beetles, have evolved the ability to assemble defensive ectosymbiotic bacteria on body surfaces to defend against fungal parasitic infections ( 25 28 ). We recently showed that the surface microbiotas assembled on Drosophila melanogaster are beneficial to hosts by inhibiting the spore germinations of entomopathogenic fungi on fly surfaces ( 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, several other rare genera of actinomycetes have been isolated from hymenopteran samples including Actinomadura ( Promnuan et al, 2009 , 2021 ), Actinoplanes ( Madden et al, 2013 ), Kitasatospora Microbacterium ( Wu et al, 2022 ), Nocardiopsis ( Promnuan et al, 2009 ; Kumar et al, 2012 ), Nocardioides ( Hanshew et al, 2015 ), Nonomuraea ( Promnuan et al, 2009 ), Phytohabitans ( Wang et al, 2020 ), Propionicimonas ( Zucchi et al, 2011 ), Pseudonocardia ( Cafaro et al, 2011 ; Meirelles et al, 2014 ; Bruner-Montero et al, 2021 ), Saccharopolyspora ( Kumar et al, 2012 ), Saccharothrix ( Matarrita-Carranza et al, 2017 ) , Streptosporangium ( Kumar et al, 2012 ; Matarrita-Carranza et al, 2017 ), Thermoactinomycetes ( Kumar et al, 2012 ), Tsukamurella ( Barke et al, 2010 ), Verrucosispora ( Wang et al, 2020 ).…”
Section: Bioprospecting Hymenopteran-associated Actinomycetesmentioning
confidence: 99%
“…Among them, Pseudonocardia is first vertically transmitted by founding queens and then transferred from workers or even from the fungal cultivar to younger workers and new queens. Other actinomycetes, including Streptomyces spp., are horizontally acquired from the environment (Batey et al, 2020 ; Bruner‐Montero et al, 2021 ; Li et al, 2018 ).…”
Section: Attina Ants Using Fungi As Foodmentioning
confidence: 99%